Examining the association between the Mediterranean diet and depression: a cross-sectional study in Lebanon - Abdel Sater, Rana F.; Younes, Rudy S.; Julien, Sofi G. (Frontiers in Nutrition, 2025)
IntroductionSociocultural practices, including traditional dietary patterns, influence mental health and depression. The Mediterranean diet (MD), which is common in many Middle Eastern countries such as Lebanon, is regarded as one of the healthiest dietary patterns available. Although the link between MD and mental health is gaining recognition, there is still a lack of substantial evidence to support this relationship.ObjectivesThis study sought to examine the relationship between depression and adherence to MD (AMD).MethodsA cross-sectional study was conducted among 525 participants through an online questionnaire that assessed the severity of depression using the Patient Health Questionnaire 9 (PHQ-9), AMD using the Mediterranean Diet Adherence Screener (MEDAS) questionnaire, and relevant sociodemographic variables. Descriptive, linear regression, and bivariate logistic regression analyses were performed to answer the research questions.Results24% of participants self-reported depressive symptoms, as indicated by a PHQ-9 score of 10 or higher, with the majority being female. The scores on the MEDAS and the PHQ-9 were significantly different between the groups classified as having depression and those without depression (7.4 ± 2.4 vs. 7.9 ± 2.5; p = 0.033) and (14.2 ± 4 vs. 5 ± 2.6; p < 0.001), respectively. The MEDAS score was inversely correlated with the PHQ-9 score (r = −0.126, p = 0.003), indicating a relationship between depression and AMD. The adjusted model indicated that consuming two or more servings of vegetables per day is associated with a decrease in the likelihood of experiencing depressive symptoms (b = −0.66, p = 0.021). Several social factors, including employment status, education level, income, and marital status, have been identified as predictors of depression.ConclusionSufficient vegetable consumption may help reduce the risk of depression. These findings could have important implications for mental health prevention and treatment.